Addition of Low-Cost Additives Improves Real Time PCR Assay of GC Rich FMR1 Region Utilizing Taqman Probe - Hikmah, E.M.; Ankathil, R.; Peng, H.B.; Zilfalil, B.A. (Japan International Cultural Exchange Foundation, 2024)
Objective: To obtain specific amplification, demonstrating that these low-cost additives can improve the amplification of the GC rich region in FMR1 gene, not only in PCR, but Real-time PCR as well. Methods: The basic reaction for the real time PCR were set up in a total volume of 20 ··l containing LightCycler ® TaqMan ® Master reaction mix (Roche Applied Science), a pair of designed primer, designed probe and genomic DNA. Other reactions were done by adding DMSO, Formamide, Betaine and 7-deaza-dGTP either individually or in combination. All the 16 PCR products of various combinations of these additives were then separated by gel electrophoresis and the selected PCR products were then sent for sequencing. Results: Combination of Betaine, DMSO and 7-deaza-dGTP generate the highest PCR product intensity as it increases the fluorescence emitted with Cp value 27.47. The most specific band out of the 16 PCR products was also obtained from this combination. Conclusion: The best combination of additives for this GC rich template is the DMSO, betaine and 7-deaza-dGTP. In determining the best combination of additives, real time PCR can be used as more accurate method than conventional PCR in terms of specificity in determining the GC rich of the 5' untranslated region of FMR1 gene. The findings also suggest that additives used in PCR are also well suited with real time PCR as no evidence of inhibition in the fluorescence signal detection were discovered.